EXPRESSIONISTIC PORTRAITS BY VASYLS TEFANYK: VISUALIZATION - Matsiak (Basa), O. M.; Bomko, L. О. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The subject of research in the article is the portraits of the characters of Vasyl Stefanyk's novels «Katrusia», «News», «Basaraby», «Stone Cross», «Sin» («Kasiyanikha thinks to herself...»). An attempt is made to reasonably translate the verbal descriptions of Katrusia, Ghandzunia and Dotsia, Basaraby, Ivan Didukh, Kasiyanikha with the illegitimate son in to the language of painting, in fact, to illustrate them, to visualize them with Bstrict adherence to the author's text and to visually prove Vasyl Stefanyk's expression istic style of writing with other elements of avant-garde.